Parameterized unit testing: theory and practice - Tillmann, Nikolai; de Halleux, Jonathan; Xie, Tao (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
Unit testing has been widely recognized as an important and valuable means of improving software reliability, as it exposes bugs early in the software development life cycle. However, manual unit testing is often tedious and insufficient. Testing tools can be used to enable economical use of resources by reducing manual effort. Recently parameterized unit testing has emerged as a very promising and effective methodology to allow the separation of two testing concerns or tasks: the specification of external, black-box behavior (i.e., assertions or specifications) by developers and the generation and selection of internal, white-box test inputs (i.e., high-code-covering test inputs) by tools. A parameterized unit test (PUT) is simply a test method that takes parameters, calls the code under test, and states assertions. PUTs have been supported by various testing frameworks. Various open source and industrial testing tools also exist to generate test inputs for PUTs. This tutorial presents latest research on principles and techniques, as well as practical considerations to apply parameterized unit testing on real-world programs, highlighting success stories, research and education achievements, and future research directions in developer testing. The tutorial will help improve developer skills and knowledge for writing PUTs and give overview of tool automation in supporting PUTs. Attendees will acquire the skills and knowledge needed to perform research or conduct practice in the field of developer testing and to integrate developer testing techniques in their own research, practice, and education.